Representasi Nilai Estetika dalam Lirik Lagu Asmalibrasi dan Implikasinya Terhadap Pembelajaran di SMA - Nur Sherina Sopianti; Arif Firmansyah (LP. Ma'arif Janggan Magetan, 2023)
he purpose of this research to describes the aesthetic value in the physical structure used in the lyrics of Soegi Bornean’s Asmalibrasi song and describes the implications of this research for learning Indonesian in high school. This research uses a qualitative description. The data source in this research is obtained from the lyrics of Asmalibrasi song by Soegi Bonean. This research uses documentary techniques, writing techniques and reading techniques. The theory used in the physical structure of Asmalibrasi song lyrics such as diction, imagery and language style used in conveying the meaning of an Asmalibrasi song lyric. This research is applied to Indonesian language learning in high school class X phase E of the Merdeka Curriculum. Implications for students' understanding of Indonesian language, cultural understanding, level of listening to lyrics and understanding meaning, and introduction to kebhinekaan Indonesia.